PKM Internasional Indonesia-Malaysia: Membangun Jiwa Kewirausahaan melalui Pembelajaran Berbasis Proyek dan Penerapan Prinsip-Prinsip Manajemen untuk Siswa Maahad Tahfidz An-Nur (MATAN) Pucong, Malaysia - Riwayani Wani; Lukman Hakim Hutagalung; Mhd Shafwan Koto; Mansur Tanjung Mansur; Nur Aisyah Zendrato (Politeknik Piksi Ganesha Indonesia, 2026)
This study aims to develop the entrepreneurial spirit of Malaysian students through project-based learning combined with the application of management principles. This method is designed to enhance students' critical thinking skills, creativity, responsibility, and decision-making abilities in an entrepreneurial context. The project-based learning approach allows students to directly design, implement, and evaluate entrepreneurial activities in a structured manner based on management principles such as planning, organizing, executing, and controlling. Implementation results indicate that this learning model is able to foster students' innovative attitudes, leadership, and self-confidence in managing their business ideas. Al-Washliyah College of Economics, Sibolga, has established a collaboration in the Tridharma of Higher Education under the number: M.A.T.A.N/047/VIII/2025. Based on this, Al-Washliyah College of Economics, Sibolga, and MATAN Pucong Malaysia conducted Community Service (PkM) activities. These findings recommend the continued integration of project-based learning and management principles to strengthen the entrepreneurship education ecosystem in Malaysian schools.